Osteosarcoma in Children: Not Only Chemotherapy - Maura Argenziano; Chiara Tortora; Elvira Pota; Alessandra Di Paola; Martina Di Martino; Caterina Di Leva; Daniela Di Pinto; Francesca Rossi (MDPI AG, 2021)
Osteosarcoma (OS) is the most severe bone malignant tumor, responsible for altered osteoid deposition and with a high rate of metastasis. It is characterized by heterogeneity, chemoresistance and its interaction with bone microenvironment. The 5-year survival rate is about 67% for patients with localized OS, while it remains at 20% in case of metastases. The standard therapy for OS patients is represented by neoadjuvant chemotherapy, surgical resection, and adjuvant chemotherapy. The most used chemotherapy regimen for children is the combination of high-dose methotrexate, doxorubicin, and cisplatin. Considered that the necessary administration of high-dose chemotherapy is responsible for a lot of acute and chronic side effects, the identification of novel therapeutic strategies to ameliorate OS outcome and the patients' life expectancy is necessary. In this review we provide an overview on new possible innovative therapeutic strategies in OS.